Nutrition, activity, and health status of elementary children - Rasmussen, Diane. (My University, 2008)
Obesity is a global concern with an alarming increase in the rate of overweight children. National statistics indicate that 18.8% of children are overweight. (Centers for Disease Control, 2004; 2007b). Limited data exists for elementary school children in Wisconsin, including Menomonie. Forty-two subjects from two elementary schools participated in the study. Height, weight, body mass index (BMI), triceps skinfold and midarm, and waist and hip circumference were measured. Subjects also completed a survey measuring nutrition knowledge, behavior, and intention as well as diversity in physical activity and attitude. Results indicated 16.7% of children in the study were overweight. Trends indicated there was an increase in the prevalence of overweight children with age as well as gender. As nutrition knowledge increased, intentions toward healthy eating behavior also increased. No correlation existed between nutrition knowledge, behavior, or intentions with respect to some components of diversity of physical activity and their attitude to be physically active. Thus effective interventions for this age group should include nutrition education as well as encouraging an active lifestyle.
Keywords: Obesity in children--Wisconsin; Children--Nutrition--Wisconsin